2013
DOI: 10.3724/sp.j.1145.2013.01069
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Determination of Monosodium Glutamate in Food Samples Using Colorimetric Determination of Monosodium Glutamate in Food Samples Using L-glutamate Oxidase-glutamate Oxidase

Abstract: A rapid, sensitive and simple chromogenic method was developed for quantitative determination of monosodium glutamate (MSG) in food samples. The method incorporated a glutamate oxidase and peroxidase. The librated H 2 O 2 from a glutamate sample as a result of enzymatic action was measured using 4-aminoantipyrine and phenol as a chromogenic reagent at 502 nm. Glutamate calibration curve was linear up to 125 mmol L -1 with a detection limit of 2 mmol L -1 . The results of analyzing L-glutamate in various food s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Isa and Ghani (2009) have developed a solid state glutamate sensor in combination with flow injection analysis and an LOD of 0.008 mol equal to 1.4 g/kg of food sample. Kampha et al (2004) and Afraa et al (2013) used an enzymatic method combined with a spectrophotometric measurement for L-glutamate in food. In the latter publication (Afraa et al, 2013), the method performance was demonstrated to be in line with internationally accepted performance criteria.…”
Section: Methods Of Analysis In Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…Isa and Ghani (2009) have developed a solid state glutamate sensor in combination with flow injection analysis and an LOD of 0.008 mol equal to 1.4 g/kg of food sample. Kampha et al (2004) and Afraa et al (2013) used an enzymatic method combined with a spectrophotometric measurement for L-glutamate in food. In the latter publication (Afraa et al, 2013), the method performance was demonstrated to be in line with internationally accepted performance criteria.…”
Section: Methods Of Analysis In Foodmentioning
confidence: 99%
“…() and Afraa et al. () used an enzymatic method combined with a spectrophotometric measurement for l ‐glutamate in food. In the latter publication (Afraa et al., ), the method performance was demonstrated to be in line with internationally accepted performance criteria.…”
Section: Assessmentmentioning
confidence: 99%
“…Then pannae were higher results than those obtained by 7,21 (1.4570 mg/Kg. ), 22,23 (1.600 mg/ Kg.) and 24,18 (1.390 mg/Kg.).…”
Section: Discussionmentioning
confidence: 99%